Приховані інтенції мовлення українських політиків на політичних ток-шоу (на прикладі виступів Ірини Геращенко, Анатолія Гриценка, Юлії Тимошенко та Арсенія Яценюка на політичному ток-шоу «Шустер Lіvе») = Hidden intentions broadcasting Ukrainian politicians on political talk shows (for example, speeches by Iryna Gerashchenko, Anatoliy Grytsenko, Yulia Timoshenko and Arseniy Yatsenyuk on the political talk-show "Shuster Live") - Borodavko, Nataliya; Maslova, Yuliya; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Borodavko Natalia, Maslova Yuliya, Zukow Walery. Приховані інтенції мовлення українських політиків на політичних ток-шоу (на прикладі виступів Ірини Геращенко, Анатолія Гриценка, Юлії Тимошенко та Арсенія Яценюка на політичному ток-шоу «Шустер Lіvе») = Hidden intentions broadcasting Ukrainian politicians on political talk shows (for example, speeches by Iryna Gerashchenko, Anatoliy Grytsenko, Yulia Timoshenko and Arseniy Yatsenyuk on the political talk-show "Shuster Live"). Journal of Education, Health and Sport. 2016;6(7):319-335. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57922 http://ojs.ukw.edu.pl/index.php/johs/article/view/3698 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. ПРИХОВАНІ ІНТЕНЦІЇ МОВЛЕННЯ УКРАЇНСЬКИХ ПОЛІТИКІВ НА ПОЛІТИЧНИХ ТОК-ШОУ (НА ПРИКЛАДІ ВИСТУПІВ ІРИНИ ГЕРАЩЕНКО, АНАТОЛІЯ ГРИЦЕНКА, ЮЛІЇ ТИМОШЕНКО ТА АРСЕНІЯ ЯЦЕНЮКА НА ПОЛІТИЧНОМУ ТОК-ШОУ «ШУСТЕР LІVЕ») Hidden intentions broadcasting Ukrainian politicians on political talk shows (for example, speeches by Iryna Gerashchenko, Anatoliy Grytsenko, Yulia Timoshenko and Arseniy Yatsenyuk on the political talk-show "Shuster Lìve") Наталія Бородавко Natalia Borodavko Юлія Маслова Yuliya Maslova Національний університет «Острозька академія» National University "Ostrog Academy" Walery Zukow Walery Zukow UMK w Toruniu UMK in Torun У статті проаналізовано виступи українських політиків – Ірини Геращенко, Анатолія Гриценка, Юлії Тимошенко та Арсенія Яценюка на політичному ток-шоу «Шустер Live» за допомогою методики фреймового аналізу. На основі цього виокремлено провідні категорії політичного тексту, на основі яких подано основні фрейми досліджуваних політичних виступів. Також, було виокремлено сценарії та скрипти цих промов. Саме ці елементи фреймового аналізу дозволили нам розкрити теми, які піднімаються у промові та правильно розставити акценти, основні мотиви мовців та провідні приховані інтенції. Ключові слова: політична промова, політичне ток-шоу, фреймовий аналіз, фрейм, скрипт, сценарій. The article analyzes the performances of Ukrainian politicians – Irina Herashchenko, Anatoliy Grytsenko, Yulia Timoshenko and Arseniy Yatsenyuk on the political talk-show "Shuster Live" using methods of frame analysis. This highlights the leading category of political text, on the basis of which are main frames investigated political appearances. Also, it was founded as the scripts and scripts of these speeches. These elements of the frame analysis allowed us to reveal the topics that are raised in a speech and accents properly, the main motives of the speakers and leading the hidden intentions. Keywords: political speech, political talk shows, frame analysis, frame, script, script.